A trajetória político-educativa de Margarida Maria Alves: entre o velho e o novo sindicalismo rural - Ferreira, Ana Paula Romão de Souza (2009)
This study's main objective is to analyze the formation of educational politics and Margarida Maria Alves (1933-1983) in his career in social movements, more focused, the rural labor movement. The aim is to also understand the social representations of race lived on his political experience in a historical period conflict between the old and the new social movements. The perspective is to focus on the cultural-historical sense of their learning and representations, built from the political-party-union and their own struggles revendicating, compared to the policies issued by the oligarchic culture during the last two decades of the twentieth . In this sense, we defend the thesis that: Margarida Maria Alves has a social character in conflict with the transition from old to new rural labor movement. And that transition was a prospect of breaks politics of subservience to an oligarchic practice combative union reflected through popular education, from the self-experience of the peasantry. Situated in the field of theoretical and methodological approaches in Social History and the New Cultural History, the mentioned approach, based on the expansion of its range of areas, particularly the so-called history of the conquered, allowed to set the historical and social universe through the categories: experience, representation and practice, among others. Therefore, we researched through multiple sources: newspapers, official documents, books and training, especially oral history. This made good marks, tracks and fragments that express the historical struggle and the life of that union, overcoming the silence of intellectual conservatism about his beliefs and his political-educational trajectory. In this scenario, where there is the undeniable richness of the performance of the peasant struggles of Paraíba, it was revealed the importance of union formation and training of gender within the territory of the rural culture, as opposed to the power struggle in a patriarchal society. Thus, the contribution of the representation of fighting in the conflict areas of social class gender directed to set new standards in teacher education practices of social movements.